456 Urinary catheterisation in the nursing home setting: challenges and opportunities in catheter use and design: a questionnaire study. (13th April 2023) - Rabi, A; McCoy, C; Mitchell, G; Parsons, C
Abstract: Introduction: Urinary catheter use is associated with a range of complications including infection, encrustation, blockage, leakage, pain and discomfort (1). There is a limited evidence-base regarding prevalence of catheterisation, and issues experienced in using urinary catheters in the nursing home (NH) population. Aim: To explore the prevalence of urinary catheterisation and the types of catheters used by NH residents in a region of the United Kingdom (UK), to investigate the most common issues associated with catheter use, and to explore urinary catheter services in NHs. Methods: Three different versions of a questionnaire for self-completion were designed (for NH managers, nurses and non-registered healthcare assistants), piloted and distributed to NH staff in a region of the UK, via post or online. NH managers were recruited through postal distribution to all registered NHs in the region (n=243) and via email distribution facilitated by a non-profit membership organisation representing health and social care providers. Nurses and healthcare assistants in 83 nursing homes across the region were recruited through a gatekeeper (GM: an academic care home nurse specialist and link-link lecturer from the School of Nursing and Midwifery, QUB. Questionnaires contained 47 items (managers), 48 (nurses), and 18 items (healthcare assistants), with a mixture of Likert scale questions, yes/no questions and a small number of open questions. Data were anonymised and entered into SPSS (V27) for statistical analysis. Descriptive analysis was conducted for closed-ended questions, and thematic analysis was used for open-ended questions. Results: Questionnaires were completed between March and June 2022 by 162 participants. Eighty-eight responses were received from NH managers (response rate = 36.2%; 88/243). Seventy-four responses were received from nurses and healthcare assistants (31 and 43, respectively). Prevalence of catheterisation among NH residents was 6.4% (206/3226) and numbers of catheter users ranged between zero and eight per NH. Most residents (78.6%; 162/206) used indwelling urethral catheters. Almost one third of NH managers (29.5%; 26/88) and nurses (32.3%; 10/31) reported that catheters cause UTIs often and almost one in ten (8.0%; 7/88 and 9.7%; 3/33, respectively) reported a UTI occurring every time a catheter is used. Two-thirds (67.0%; 59/88) of NH managers and 58.1% (18/31) of nurses reported that catheter care training is not mandatory for all staff. Most managers and nurses agreed or strongly agreed that they had adequate catheter training in the past (80.7%; 71/88 and 74.2% 23/31, respectively), but less than half of managers and nurses reported good availability of catheter care retraining (45.5%; 40/88 and 48.4%; 15/31, respectively). Around 64.8% (57/88) of managers and 71.0% (22/31) of nurses wanted catheters to be reviewed more often than they currently are. NH managers and nurses reported difficulty in contacting specialists regarding catheter-associated problems in complex cases; only one third of managers and nurses indicated this was easy or very easy (34.1%; 30/88 and 38.7%; 12/31, respectively). Improvements to catheter design were not considered feasible by many respondents; approximately one third of managers, nurses and healthcare assistants thought improvements could be made (35.2%; 31/88, 32.3%; 10/31 and 30.2%; 13/43, respectively). Conclusion: These findings highlight issues in catheter care training and management of catheter-related complications in the NH setting. Providing all NH staff, including healthcare assistants, with adequate urinary catheter training in managing catheter-associated complications has the potential to improve patient quality of life and reduce unplanned hospital visits and represents a priority for research and clinical practice. This study is the first to examine catheter prevalence and issues with use in NHs in this region of the UK. However, findings may not be generalisable to other parts of the UK or internationally. References: 1. Feneley RC, Hopley IB and Wells PN. Urinary catheters: history, current status, adverse events and research agenda. J Med Eng Technol. 2015 Sep;17(8):459-70.